Is cervicodynia associated with head load carrying in construction site workers in Lucknow - Dev Prakash; Vipin Kumar; Shalabh Varshney; Ahmad Ayaz; Srijan Kapoor; Girish Kumar Singh (Asian Journal of Medical Sciences, 2023)
Background: Cervicodynia is one of the most common musculoskeletal symptoms reported by construction workers, particularly those involved in head-load carrying jobs. One of the reasons for this could be accelerated degenerative changes in the cervical spine as a result of continuous stress on it owing to head-load carrying. Apart from carrying a heavy load on the head, frequently have to work in an awkward posture involving “repeated movement of the back and limbs and work above the shoulder during loading on the head and unloading as well as stacking bricks.” In response to the continuous stresses on the neck muscles, Cervicodynia is a commonly occurring phenomenon among construction workers, particularly head-load carrying workers. Aims and Objectives: This cross-sectional study aims to determine the association between cervicodynia and head-load carrying in construction site workers in Lucknow. Materials and Methods: A total 68 workers were enrolled in the study and their details were recorded in the questionnaire Pro forma and they were asked to provide their job details. Those workers responding affirmatively to cervicodynia, the intensity, and its distribution along the brachial plexus and vertigo was recorded. Data were recorded on a separate case recording sheet, and statistical analysis was done using SPSS Version 21.0 statistical Analysis Software. The values were represented in number (%) and Mean±SD. The Chi-square test and Student’s “t” test was used. The level of significance was P<0.05. Results: Out of 68 workers, 57.4% were male, whereas 42.6% were female with a mean age of 32.15 years. The overall complaints of neck pain were 55.9%. Workers with complaints of neck pain carry significantly higher weight per round, carry weight for significantly longer duration, and cover significantly longer distance with weight. Conclusion: It can be concluded that cervicodynia is a common occurrence among construction workers, particularly, head-load carriers. Although univariate analysis highlighted the role of occupational factors in the occurrence of neck pain, on multivariate assessment, only age emerged as an independent predictor.